KAJIAN KERUGIAN RISIKO BANJIR PADA SUNGAI KRUENG MEUREUBO - Ahmad Zikra Jumhasla Putra; Masimin Masimin; Eldina Fatimah (Prodi Magister Teknik Sipil Unsyiah, 2018)
Krueng Meureubo River is one of the big river through the West Aceh district. Krueng Meureubo River has a length of ± 188 km and a catchment area of 1.632 km2. The aims of this study is to conducting inundation and the value of losses caused by floods in Krueng Meureubo river. The scope of this study includes analysis of rainfall plans, flood discharge plans, and the value of losses caused by floods. Based on data processing at 4 (four) rain stations, the annual maximum annual rainfall is obtained at each station for 10 years. Analyzing the frequency of rainfall data plan is by using several distributions, namely: Distribution Distribution Gumbel Type I, Distribution Distribution Log Pearson Type III, Distribution Normal Distribution and Distribution Log Normal. The results of the distribution test analysis to estimate the magnitude of the flood discharge with a certain repeat period, the rainfall data is closer to a distribution, calculation of Distribution and Smirnov-Kolmogorof test of each station to produce a rainfall plan. Based on the result of the test by using Smirnov-Kolmogorof test shows the suitable distribution is following the Log Pearson distribution III. Analyzing the estimated flood discharge on the Krueng Meureubo catchment area determine with a 2-year, 5-year, 10-year, 25-year, 50-year and 100-year re-period. The peak flood discharge estimated by using Hidrograf Satuan Sistetis (HSS) Gama I. The inundation area is obtained from the height of the flood from the cross section of the Krueng Meureubo river. The cross section used in this study is the cross section of KN 7 located in Rundeng village, Johan Pahlawan sub district. The value of losses due to floods that occur when the discharge of Q100 year (1,516 m3 / s) is Rp468.098.453.000, - which consists of loss of damage to residents settlements and rice fields.